Hypsarhythmia or Hypsarrhythmia? - John J. Millichap; J. Gordon Millichap (Pediatric Neurology Briefs Publishers, 2015)
Hypsarhythmia was originally spelled with one 'r' by Drs Frederick and Erna Gibbs when they coined the term in 1952.